Unrevealed Depression Involves Dysfunctional Coping Strategies in Crohn’s Disease Patients in Clinical Remission - Caterina Viganò; Roberta Calzolari; Paola Marianna Marinaccio; Cristina Bezzio; Federica Furfaro; Gabriella Ba; Giovanni Maconi (Gastroenterology Research and Practice)
Background and Aims. This study investigated the proportion of CD patients in clinical remission with clinical depression, and coping strategies in those with severe depressive disorders. Materials and Methods. One hundred consecutive CD patients in clinical remission were screened for anxiety and depression by using Hospital Anxiety and Depression Scale and patients with depressive symptoms were further investigated by means of Cognitive Behavioural Assessment 2.0 and Beck Depression Inventory (BDI). Afterwards the coping strategies were assessed through the Brief-COPE questionnaire. Results. Twenty-one patients had anxious symptoms and 16 had depressive symptoms with or without anxiety. Seven of these patients (43.8%) showed significant depressive symptoms. Compared to patients without psychiatric disorders, these patients showed significant lower score in “positive reframing” (p: 0.017) and in “planning” (p: 0.046) and higher score in “use of instrumental social support” (p<0.001), in “denial” scale (p: 0.001), and in “use of emotional social support” (p: 0.003). Conclusions. Depressed CD patients in clinical remission may have dysfunctional coping strategies, meaning that they may not be able to implement functional strategies to manage at best stress related with their disease.